2001
DOI: 10.1074/jbc.m008916200
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Down-regulation of the Type I Inositol 1,4,5-Trisphosphate Receptor and Desensitization of Gonadotropin-releasing Hormone-mediated Ca2+ Responses in αT3–1 Gonadotropes

Abstract: Despite no evidence for desensitization of phospholipase C-coupled gonadotropin-releasing hormone (GnRH) receptors, we previously reported marked suppression of GnRH-mediated Ca 2؉ responses in ␣T3-1 cells by pre-exposure to GnRH. This suppression could not be accounted for solely by reduced inositol 1,4,5-trisphosphate (Ins(1,4,5)P 3 ) responses, thereby implicating uncoupling of Ins(1,4,5)P 3 production and Ca 2؉ mobilization (McArdle, C. A., Willars, G. B., Fowkes, R. C., Nahorski, S. R., Davidson, J. S., a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 35 publications
1
54
0
Order By: Relevance
“…3) Fig. 3), the wild-type GnRHRs mediated the anticipated robust increase in [Ca 2+ ] i (see also Hislop et al 2001, Willars et al 2001) and a similar response was seen in cells transfected with the h.XtGnRHR construct. No such increase was seen in cells transfected with the h.XlGnRHR although this may simply reflect low expression of the receptor (results not shown).…”
Section: Resultsmentioning
confidence: 91%
“…3) Fig. 3), the wild-type GnRHRs mediated the anticipated robust increase in [Ca 2+ ] i (see also Hislop et al 2001, Willars et al 2001) and a similar response was seen in cells transfected with the h.XtGnRHR construct. No such increase was seen in cells transfected with the h.XlGnRHR although this may simply reflect low expression of the receptor (results not shown).…”
Section: Resultsmentioning
confidence: 91%
“…As this occurs in the absence of receptor desensitisation and is not attributable to depletion of the intracellular Ca 2+ pool, it appears to reflect a reduction in the efficiency with which IP 3 mobilises Ca 2+ from this pool (McArdle et al 1996). This effect was associated with, and apparently dependent upon, a GnRH-stimulated reduction in the number of IP 3 receptors (IP 3 -Rs) (Willars et al 2001). Sustained activation of several PLC-activating GPCRs has been shown to cause IP 3 -R down-regulation, an effect attributed to the ligand-stimulated ubiquitinylation and consequent proteolysis of the activated IP 3 -R (Wojcikiewicz & Oberdorf 1996, Zhu & Wojcikiewicz 2000.…”
Section: Desensitisation Downstream Of the Gnrh-rmentioning
confidence: 97%
“…80% reduction within 20-30 min). Thus it appears that this receptor, which is atypically resistant to desensitisation, is atypically efficient at provoking this novel form of post-receptor desensitisation (Willars et al 2001). It is important to recognise, however, that the relevance of this effect to desensitisation of gonadotrophin secretion has not been established.…”
Section: Desensitisation Downstream Of the Gnrh-rmentioning
confidence: 99%
“…Therefore upon stimulation the Type I GnRH receptor chronically activates phospholipase C-␤. It has, however, been demonstrated that there is a regulatory process upon GnRH-mediated signaling at the level of inositol trisphosphate receptor activation and subsequent intracellular calcium mobilization (3). The protracted GnRH receptor stimulation causes a physical downregulation of the intracellular inositol trisphosphate receptors in the gonadotrope resulting in a curtailment upon any successive ligand-mediated intracellular Ca 2ϩ pulses.…”
mentioning
confidence: 99%